PENERAPAN MOTIF BUNGA MATAHARI DAN BUNGA TERATAI DENGAN TEKNIK 3D PRINTING DALAM PENCIPTAAN PERHIASAN DI UD. ROMO CELUK,SUKAWATI GIANYAR - I Nyoman Yudhi Satriawan; I Ketut Muka; I Made Mertanadi (Hastagina : Jurnal Kriya Seni, 2022)
Internships are practical activities for students with the aim of gaining experience from these activities, which can later be used as professional development for students. This activity is carried out directly in the real world of work. As for this internship, the creators did it at UD. Father Celuk, Sukawati Gianyar Bali. This place of business is engaged in jewelry, especially silver. The method of creation used in the creation of the work of this internship process is through two intuitive approaches, and through a scientific method that has been carefully planned, analytically and systematically. In the method refers to the theory of creation proposed by SP. Gustami in his book entitled "the process of creating craft art: methodological strands" explains the process of creating craft works through three pillars of creation such as exploration, experimentation, and formation. Gustami, 2004:31 (in Kusyati, 2019:22). The concept of creating this work is to make works in the form of jewelry which is the result of the learning process that is obtained at the internship. The process of creating works in the form of jewelry is carried out through the design stage, namely exploring the ideas that will be created. Next is the manufacturing process, namely through the steps of making alternative designs, 3d designs and printing. The result of this work is a master 3D of earring jewelry by applying lotus and sunflower motifs.